Helmholtz-Structured Two-Dimensional Super-Diffraction Meta-Lens - Li, He-He; Zheng, Bo; Duan, Mu-Sen; Han, Feng; Hu, Yun-Xin; Li, Xiao-You; Qian, Si-Yu; Chen, Xue-Feng; Liu, Sheng-Chun (Frontiers in Physics, 2022)
Focusing beyond the acoustic diffraction limit has always been expected especially in acoustic imaging, ultrasonic therapy and other fields. Manipulating the acoustic waves beyond the diffraction limit offers an alternative application potential in high-resolution imaging and medical ultrasound diagnosis and treatment. Here, we present a two-dimension circular meta-lens with sub-wavelength acoustic Helmholtz resonators to implement the super-diffraction focusing. The proposed acoustic meta-lens consists of 28 units of hybrid structure possessing the ability to yield an arbitrary phase shift while maintains the impedance matching to provide the high sound transmission efficiency. The simulation and experimental results show that the designed acoustic meta-lens can realize the subwavelength sound focusing beyond the diffraction limit. The proposed method can greatly promote the application and development of acoustic superfocusing technology in acoustic imaging, particle manipulation and other fields.